EFEITO DO GRUPO GENÉTICO DO BEZERRO SOBRE A EFICIÊNCIA ENERGÉTICA DE VACAS NELORE EM PASTEJO - SOUSA, Estácio Lopes; SILVA, Camila de Souza; SANTOS, Diego Magnum Malfrede dos; SILVA, Thomás Henrique Roque da; LIMA, Josilaine Aparecida da Costa; FERNANDES, Henrique Jorge (ANAIS DO ENIC, 2020)
-